(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2023)
This paper presents the concept of postdigital as a lens from which to approach and examine our immediate cultural present. For this purpose, it proposes an analysis of the term, as well as of the relationships it establishes with other philosophical concepts and concludes by examining its most immediate links with the development of current (digital) culture and the possibilities it offers in this context. A description of the notion of postdigital is thus established that moves away from the disruptive and deterministic definition that commonly accompanies technological discourse, in favour of a critical look at the structure and scientific development that underlies the current network-society. A social paradigm that not only generates connections and public spaces but also a change of conception of how the media are structured and who has access to them. It concludes by understanding the postdigital perspective as necessary to understand and question our current present, proposing to reflect on collective modes of thought and action to generate an ecopedagogy of knowledge.